Developing efficient small molecule-based organic photo-couplers by optimizing the cathode interfacial layer in the photodetector. Issue 16 (6th April 2023) - Estrada, Richie; Luo, Dian; Lee, Chih-Chien; Iskandar, Johan; Biring, Sajal; Al Amin, Nurul Ridho; Akbar, Abdul Khalik; Chen, Chih-Hsin; Yu, Chang-Wei; Pham, Tran My Dung; Liu, Shun-Wei
Abstract : Thorough electrical and optical characterizations are carried out herein to investigate the phenomena of thermionic field emission, trap density, and exciton quenching, which justifies the superior performance of the proposed organic photo-coupler. Abstract : An organic photo-coupler (OPC) is one of the optoelectronic devices that is packaged face-to-face with electrically isolated input and output components. Substantially, the performance of OPC depends on the detection capability of an organic photodetector (OPD) when irradiated by an organic light-emitting diode (OLED). When illuminated, a tandem OLED transmits light with a wavelength of 560 nm. Four different hole blocking layers (HBLs) in OPD structures, i.e., BPhen, 10 nm thick C60, 20 nm thick C60, and C60 :LiF, are investigated to achieve a low dark current density, high current transfer ratio (CTR), higher cut-off frequency, and fast photo-response pulse of the OPC. Overall, at an applied bias of −3 V, the small molecule-based OPC demonstrates the lowest dark current density (OPC D) down to the level of 3.642 × 10 −9 A cm −2, CTR (OPC A) above 18%, a wide cut-off frequency in the range of 644 kHz (OPC A) ≤ f −3dB ≤ 708 kHz (OPC D), and a transient photo-response faster than 500 ns at a frequency of 600 kHz. The thorough electrical and optical characterization carried out in this study is expected to pave the way for developing optimized OPCs for practical applications.